Comparative analysis of rhamnolipid congener synthesis in neotype Pseudomonas aeruginosa ATCC 10145 and two marine isolates. (August 2019) - Du, Jin; Zhang, Aijun; Zhang, Xiaoqing; Si, Xiaoguang; Cao, Junrui
Highlights: Two rhamnolipid producing marine P. aeruginosa isolates were compared with neotype. The proportion of congeners with C10 -C12 /C10 -C12:1 and/or di-rhamnose was higher. The HAA and fatty acid content showed sufficient composition of C12 and C12:1 . The expression of rhlAB and rhlC was elevated throughout the fermentation process. Synthesis of the precursors was enhanced at the onset of rhamnolipid accumulation. Abstract: A comparative study of rhamnolipid congener synthesis was performed using the neotype Pseudomonas aeruginosa ATCC 10145 and two marine isolates (1A01151 and 1A00364). Compared with the neotype, 1A01151 and 1A00364 showed increased production of rhamnolipids containing higher proportion of congeners with longer fatty acid chains (C10 -C12 and C10 -C12:1 ) and/or di-rhamnose moiety. These could reduce surface tension of water to lower minimum values of 21.3 mN m −1 and 25.7 mN m −1 . The comparative profile of rhamnolipid congener composition, fatty acid content and gene expression suggested that elevated expression of rhlAB and rhlC throughout the fermentation process and enhanced accumulation of dTDP-l -rhamnose and fatty acid precursors (C12 and C12:1 ) at the onset of rhamnolipid accumulation were related to improved rhamnolipid production and surface-active property. This work provides insights into the metabolic relationship between rhamnolipids and related precursor biosynthesis, and could therefore be beneficial for process optimization for efficient rhamnolipid congener production.